Absence Without Official Leave Among Special Action Force Personnel: Strategies and Resolution - Cabardo, Alvin Marqueses (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Absence Without Official Leave (AWOL) has been an emerging issue in various organizations, including the Philippine National Police (PNP) Special Action Force (SAF) unit. Personnel going AWOL create gaps in the workforce which strain available resources, disrupt cohesiveness within the unit, and compromise the effectiveness of vital operations. This study sought to identify strategies for mitigating absence without official leave (AWOL) among Special Action Force (SAF) personnel, recognizing its multifaceted impact on the organization and its operations. Specifically, it aims to determine the sociodemographic profile, examine how the challenges faced by SAF personnel contribute to the increasing number of AWOL cases, identify the degree of the problems met by SAF personnel, analyze if there is a significant relationship between the extent of challenges and the degree of problems met in the AWOL status of SAF personnel and ascertain frameworks of strategies and resolutions for SAF units as mechanisms to control AWOL status. The study involved a quantitative survey research design where questionnaires were used to collect data from a total of 240 respondents. Frequency, percentage distribution, means, Pearson Moment Correlation Coefficient was used using Statistical package for social sciences (SPSS). Results imply that there is no relationship between the difficulties AWOL SAF members face and the extent of issues they encounter into. Personal circumstances including family problems, mental health challenges, or dissatisfaction with work conditions frequently have an impact on AWOL incidents. This emphasizes how complicated AWOL incidents can be and how important it is to take each situation and motivations into account when dealing with them. This indicates the need to implement more programs that will address their needs, boost their morale and will promote work-life balance activities.